PROBLEMS OF MAHAYANA DEVELOPMENT IN TANGERANG: A CASE STUDY IN PADUMUTTARA MONASTERY - Nyoto, Nyoto (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
This study aims to find out why Padumuttara monastery followers carry out the Mahayana tradition. This research is descriptive qualitative research. In order for the data obtained to be satisfactory, the authors conducted observations, interviews, and documentation so that the data obtained was accurate. Research on the existence of Mahayana at Padumutara monastery is that people carry out various Mahayana traditions because of teacher guidance, preserving culture and Buddha Dharma, containing teachings of love. In addition, the Mahayana tradition developed at the Padumuttara monastery due to the support from the management of the temple and the Boen Tek Bio Temple. The Mahayana tradition also experiences various obstacles such as language problems, ritual processions, and the lack of interest of the younger generation to participate in Mahayana ritual activities.